Evaluation of polymerization shrinkage, polymerization shrinkage stress, wear resistance, and compressive strength of a silorane-based composite: A finite element analysis study - Suresh Mitthra; Kothandaraman Rajkumar; Sekar Mahalaxmi (Wolters Kluwer Medknow Publications, 2017)
Background: Understanding the mechanical properties is important in predicting the clinical behavior of composites. Finite element analysis (FEA) evaluates properties of materials replicating clinical scenario. Aim: This study evaluated polymerization shrinkage and stress, wear resistance (WR), and compressive strength (CS) of silorane in comparison with two methacrylate resins. Settings and Design: This study design was a numerical study using FEA. Materials and Methods: Three-dimensional (3D) models of maxillary premolar with Class I cavities (2 mm depth, 4 mm length, and 2.5 mm width) created and restored with silorane, nanohybrid, and microhybrid; Groups I, II, and III, respectively. Loads of 200-600 N were applied. Polymerization shrinkage was first determined by displacement produced in the X, Y, and Z planes. Maximum stress distribution due to shrinkage was calculated using AN SYS software. 3D cube models of composite resins were simulated with varying filler particle size. Similar loads were applied. WR and compressive stress were calculated: K W L/H and load/cross-sectional area, respectively. Statistical analysis done using one-way ANOVA, Kruskal-Wallis, and Tukey's honestly significant difference test (P < 0.05). Results: Polymerization shrinkage (0.99%) and shrinkage stress (233.21 Mpa) of silorane were less compared to microhybrid (2.14% and 472.43 Mpa) and nanohybrid (2.32% and 464.88 Mpa). Silorane (7.92×/1011 μm/mm3) and nanohybrid (7.79×/1011) showed superior WR than microhybrid (1.113×/1017). There was no significant difference in compressive stress among the groups. Conclusion: Silorane exhibited less polymerization shrinkage and shrinkage stress compared to methacrylates. Silorane and nanohybrid showed greater WR compared to microhybrid. CS of all groups was similar.